ANALISIS KESESUAIAN EKOWISATA MANGROVE DESA KAHYAPU PULAU ENGGANO - Desi Fitriana; Yar Johan; Person Pesona Renta (JURNAL ENGGANO)
The purpose of this study was to identify the potential of mangrove ecosystems as mangrove ecotourism objects and calculate suitability mangrove ecotourism in the village Kahyapu Enggano . This research was conducted using survey methods, measurements in the field and ecological suitability determination based on the multiplication of weights and scores obtained from any of the parameters consisting of five parameters: the thickness of the mangrove , mangrove density , types of mangrove , tidal and biota object . Mangrove ecosystem in the Village Kahyapu Enggano has the potential to be developed as an ecotourism mangrove . Based on the results, the results of IKW ( Travel Suitability Index ) at the stations I 60 % category S2 (Match ) , Station II 66 % category S2 (Match ) and Station III 71 % category S2 (Match ).